Analysis of the Difficulties of High School Students in Improving Problem Solving Ability in Physics Learning - Nova Allysa Qotrunnada (Indonesia Emerging Literacy Education, 2022)
Problem solving skills are very important in the learning process and in everyday life. This study was conducted with the aim of analyzing what factors cause high school students to have difficulty in improving problem solving skills in physics learning. The method used is a Literature Study with qualitative analysis and reviewed 40 journals or articles in the period 2018-2022, journals obtained through Publish or Perish on the Scopus and Google Scholar databases which are certainly from trusted journals. The results obtained in this study are that the models and learning media used must be relevant because they are important factors that must be considered first in improving the problem solving abilities of high school students. In addition, students are only able to write what is known and asked, without knowing how to solve and students also still have difficulty in distinguishing the equations of physics formulas that will be used in solving problems. Efforts to improve problem solving are to use relevant learning models, such as those used by researchers from the literature study that we have done, namely PBL, PjBL, Inquiry and Discovery Learning. And STEM-based learning has also been shown to be effective in several studies to improve the problem-solving abilities of high school students in physics. And students also need a lot of practice in solving problem solving problems.